Depotentiation of associative plasticity is intact in Parkinson's disease with mild dyskinesia. (June 2022) - Kishore, Asha; James, Praveen; Rajeswari, Parvathy; Sarma, Gangadhara; Krishnan, Syam; Meunier, Sabine; Popa, Traian
Abstract: Objective: Depotentiation of homosynaptic plasticity of the primary motor cortex (M1) is impaired in patients with Parkinson's disease (PD) who have developed dyskinesias. In this exploratory study, we tested whether this holds true for heterosynaptic plasticity induced by paired associative stimulation (PAS). Methods: Dyskinetic (n=11) and Non-dyskinetic (n=11), levodopa-treated PD patients were tested in M1 with PAS25 ms alone, PAS25 ms preceded by continuous theta-burst stimulation of the cerebellum (cTBSCB -PAS) as a method to evoke a larger plastic response in M1, and each of these two interventions followed by a depotentiation protocol (cTBS150 pulses ) to M1. Results: PAS25 ms and cTBSCB -PAS25 ms induced long-term potentiation (LTP)-like responses in both groups of PD patients, with cTBSCB significantly boosting the plastic response. Both these LTP-like responses could be depotentiated by cTBS150, in both groups of patients. Conclusions: Cerebellar stimulation enhances heterosynaptic plasticity in PD irrespective of dyskinesias. Depotentiation mechanisms of heterosynaptic plasticity are preserved in PD patients, including those with dyskinesias. The lack of depotentiation of LTP-like plasticity as a hallmark of dyskinesia in PD patients is not absolute. The ability to depotentiate LTP-like plasticity may potentially depend on the type of plasticity induced (homosynaptic or heterosynaptic), the circuits involved in these responses and the adequacy of dopaminergic stimulation. Highlights: Depotentiation of heterosynaptic M1 plasticity (PAS) is intact in dyskinetic PD. Lack of depotentiation in dyskinetic PD applies only to homosynaptic M1 plasticity. The anti-dyskinetic effect of cerebellar inhibitory stimulation could occur by depotentiation in M1.